Gastrocolic fistula caused by transverse colon cancer: a case report - Tomoyuki Sugi; Masanao Kurata; Tomoaki Furuta; Osamu Ishibashi; Satoshi Inagawa; Hiroyuki Ariga; Junya Kashimura; Hitomi Kawai; Norio Takayashiki; Tatsuya Oda (Surgical Case Reports)
Abstract Background A gastrocolic fistula is an unusual communication between the colon and the stomach. Although colon cancer is the most common malignant cause of gastrocolic fistula in the Western world, the incidence of gastrocolic fistula due to colon cancer is 0.3% in operated cases. Case presentation A 68-year-old man presented with anorexia, general malaise, weight loss, and vomiting of fecal matter. Investigations revealed that the patient had a large nonmetastatic splenic flexure tumor that was diagnosed as colon cancer and had invaded the stomach and pancreas. An upper gastrointestinal series confirmed a gastrocolic fistula. Left hemicolectomy, distal gastrectomy, distal pancreatectomy, and splenectomy were performed. Histology revealed transverse colon cancer, which was UICC stage (8th edition) pT4bN1bcM0 pStage IIIC. Adjuvant chemotherapy was not performed. There was no recurrence or metastasis one year after surgery. We reviewed 17 cases including our case of a gastrocolic fistula caused by colon cancer. Neoadjuvant chemotherapy was not given to any of the patients, and en bloc resections were conducted in all cases. Adjuvant chemotherapy was given to almost all of the patients. There was no recurrence or metastasis. Conclusions For gastrocolic fistula caused by advanced colon cancer, secure en bloc surgical resection was the initial treatment in all 17 reported cases including the present case, and adjuvant chemotherapy may contribute to a better prognosis.